LEMONGRASS ESSENTIAL OIL SHOWS AN ANTIPROLIFERATIVE EFFECT ON LUNG CANCER CELLS AND ITS ROLE IN EXPRESSION OF P53 GENE - Abdulhasan, G. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was aimed to investigate the antiproliferative effect of lemongrass essential oil (LEO) from Cymbopogon citratus on A549 cell line and their effect on the expression of p53 gene in lung cancer cells. The LEO was extracted and anlaysed using GC-MS analysis, the cytotoxicity of LEO against lung cancer cells was examined using MMT assay and finally the expression of p53 was determined via qRT-PCR. The chromatogram of GC-MS exhibited 14 compounds in ELO, the major one is citral (56.4%). The cytotoxicity of LEO was dose dependent which proliferation of the lung cells were significantly inhibited with increased concentration of essential oil (P≤ 0.01) as well as the IC50 was 29.13 ppm. Furthermore, it showed that cell treated with IC50 of LEO had a significant higher gene expression (P≤ 0.05) in the fold of p53 expression than untreated cells with change fold of 4.47±0.7. In conclusion, C. citratus essential oil have been found to possess antiproliferative activity against lung cancer cells and upregulation of p53 gene which can be considered a promising treatment for lung cancer patients.